2014
DOI: 10.15288/jsad.2014.75.328
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Self-Report Alcohol Misuse Measures

Abstract: ABSTRACT. Objective: Self-report measures of alcohol misuse and alcohol use disorders are valuable assessment tools for both research and clinical practice settings. However, readability is often overlooked when establishing the validity of these measures, which may result in measures written at a reading-grade level that is higher than the ability level of many potential respondents. The aim of the current study was to estimate the reading-grade level of validated measures of alcohol misuse and associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, there are no reports on the use of individualised measures in the field of substance use disorder treatment, nor do we know how this population perceives such measures. Third, the literature has suggested that the majority of measures and patient-focused materials in substance use disorder treatment tend to require literacy skills above the average level of literacy among this population [ 26 , 27 ]. However, those who are most likely to have low reading / writing skills (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no reports on the use of individualised measures in the field of substance use disorder treatment, nor do we know how this population perceives such measures. Third, the literature has suggested that the majority of measures and patient-focused materials in substance use disorder treatment tend to require literacy skills above the average level of literacy among this population [ 26 , 27 ]. However, those who are most likely to have low reading / writing skills (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to remove question numbers was made because the CLI, in particular, proved highly sensitive to the inclusion of question numbering, and scores were more consistent with other formulas when numbering was removed. We only included response options if they were provided as full sentences, instead of numerical or Likert-type response categories consisting only of a few words [ 37 ]. However, where some response sets within the same questionnaire consisted of full sentences while other response sets did not, we still included the latter to maintain a consistent approach within the same questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Whether researchers have used the Flesch readability formulas or more recently developed text-analysis approaches, conclusions across investigations have been consistent—the readability of self-report questionnaires of depression (McHugh & Behar, 2009), anxiety (McHugh et al, 2011), alcohol misuse (McHugh et al, 2014), and binge-eating disorder (Richards et al, 2013) vary widely, and some questionnaires are less appropriate for assessing individuals of limited literacy. Given that gambling disorder disproportionally affects individuals from populations who are at risk for limited reading abilities, researchers and clinicians would benefit from understanding how advanced text-analysis tools can inform the development and selection of self-report questionnaires of gambling disorder symptoms.…”
Section: Operationalizing Readabilitymentioning
confidence: 99%
“…Traditional efforts to operationalize readability used simple text characteristics such as sentence and word length as part of readability "formulas" that could be manually computed by the average reader (Flesch, 1948). Although these approaches continue to be used widely (e.g., McHugh et al, 2014), their application to the analysis of questionnaire readability has been criticized in light of the availability of modern text-analysis approaches (Lenzner, 2014). The purpose of this article was to demonstrate how modern readability approaches can be used to develop and select self-report questionnaires of psychological disorder symptoms.…”
mentioning
confidence: 99%